If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = (x + -5)(x + 6)(x + 2) Multiply f * x fx = (x + -5)(x + 6)(x + 2) Reorder the terms: fx = (-5 + x)(x + 6)(x + 2) Reorder the terms: fx = (-5 + x)(6 + x)(x + 2) Reorder the terms: fx = (-5 + x)(6 + x)(2 + x) Multiply (-5 + x) * (6 + x) fx = (-5(6 + x) + x(6 + x))(2 + x) fx = ((6 * -5 + x * -5) + x(6 + x))(2 + x) fx = ((-30 + -5x) + x(6 + x))(2 + x) fx = (-30 + -5x + (6 * x + x * x))(2 + x) fx = (-30 + -5x + (6x + x2))(2 + x) Combine like terms: -5x + 6x = 1x fx = (-30 + 1x + x2)(2 + x) Multiply (-30 + 1x + x2) * (2 + x) fx = (-30(2 + x) + 1x * (2 + x) + x2(2 + x)) fx = ((2 * -30 + x * -30) + 1x * (2 + x) + x2(2 + x)) fx = ((-60 + -30x) + 1x * (2 + x) + x2(2 + x)) fx = (-60 + -30x + (2 * 1x + x * 1x) + x2(2 + x)) fx = (-60 + -30x + (2x + 1x2) + x2(2 + x)) fx = (-60 + -30x + 2x + 1x2 + (2 * x2 + x * x2)) fx = (-60 + -30x + 2x + 1x2 + (2x2 + x3)) Combine like terms: -30x + 2x = -28x fx = (-60 + -28x + 1x2 + 2x2 + x3) Combine like terms: 1x2 + 2x2 = 3x2 fx = (-60 + -28x + 3x2 + x3) Solving fx = -60 + -28x + 3x2 + x3 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -60x-1 + -28 + 3x + x2 Simplifying f = -60x-1 + -28 + 3x + x2 Reorder the terms: f = -28 + -60x-1 + 3x + x2
| (x^2-6x+18)(x+1)= | | 0.4x+4.9=3.9 | | -2(1-8k)=126 | | 2a-7a=2a | | (5x+6)(4y-5)= | | 5(6x-4)=220 | | -5x+1=12x+1 | | R-4=-9+r | | -5x+1=112x+1 | | -2(v-7)=22-6v | | 5a=x | | 2x+3(2-7)=9 | | y(y-1)=-6 | | -4n-5(n-4)=92 | | 1xf=7 | | 2(5)-(14-5)=x | | 2N-9N=6N+52 | | 168=4(-5p+7) | | 2(5)-(14-5)=1 | | 2p+3p=10 | | [x-(3+3i)][x-(3-3i)]= | | -15-3k=-1+4k | | 3x^2+2x-49=0 | | 4x-2=22-8r | | 6=-2n+8n | | -12=-(5x-8)+8(2x-8) | | 10=1+3v-6v | | 2b+12=3b-31 | | 24=6x-2x | | Z+1.5=-2.5 | | 21=-4a+7a | | 5(s+2)=7(s-1) |